Student Autonomy and Peer Learning – An Example - Stefan Hellmer (Högre Utbildning, 2012)
This short article presents and describes a transition from “traditional” teaching with knowledge transferred from the teacher to the students in a classroom to a peer-to-peer situation in which the students, with different support, learn from each other. The process and results are encouraging and the peer-to-peer approach will be used and developed further in economics courses.